Mind the Gaps: Shortfalls in Studies of the Intraspecific Genetic Diversity of Plants Across the Gran Chaco - González, María Laura; Camps, Gonzalo Andres; Sérsic, Alicia Noemí; Cosacov, Andrea; Acosta, Maria Cristina; Aguilar, Dana Lucía; Almirón, Noelia E.A.; Chiapero, Ana Laura; Lopez Lauenstein, Diego; Scaldaferro, Marisel Analía; Sosa-Pivatto, Maria; Via do Pico, Gisela; et al. (Wiley, 2025)
Intraspecific genetic diversity (IGD) is a fundamental component of biodiversity, essential for understanding the evolutionary histories and demographic processes of species, and is key to effective conservation planning. However, ecologically important regions such as the Gran Chaco, South America's second-largest forested biome, remain largely underexplored. Encompassing diverse vegetation across climatic and altitudinal gradients, it harbours more than 3400 vascular plant species, 11% of which are endemic. Despite its ecological importance, genetic research in the region is limited and often biased. We reviewed IGD studies on vascular plants in the Gran Chaco from 1985 to 2024, identifying 85 studies covering 74 species. Coverage remains alarmingly low, with only 2.14% of species and 9.95% of the phylogenetic diversity represented. Research is skewed towards perennial (91%) and tree (46%) species, with limited representation of annuals and herbaceous taxa. Most studies relied on nuclear DNA (66%), fewer used chloroplast DNA (27%) and only 7% combined both genomes. Geographically, 33% of the Gran Chaco has no IGD data, and a further 22% includes data from a single species. Genetic sampling is concentrated in more accessible areas with higher road density and proximity to research institutions, particularly at higher altitudes. We found that in the Argentine Chaco ecoregions, 4.4 species have been genetically studied for every 100 species recorded, while in the Bolivia and Paraguay Chaco ecoregions, this proportion drops to 1.1 species for every 100 in each country. Future research on IGD in the Gran Chaco should broaden its taxonomic scope, diversify genomic tools and expand geographic coverage. Addressing these gaps will provide critical insights into the biogeographic history of the Gran Chaco and strengthen conservation strategies in this threatened and understudied biome.